Extensive gene gain associated with adaptive evolution of poxviruses - Mc Lysaght, Aoife (My University, 2003)
Previous studies of genome evolution usually have involved one or two genomes and have thus been limited in their ability to detect the direction and rate of evolutionary change. Here, we use complete genome data from 20 poxvirus genomes to build a robust phylogeny of the Poxviridae and to study patterns of genome evolution. We show that, although there has been little gene order evolution, there are substantial differences between poxviruses in terms of genome content. Furthermore, we show that the rate of gene acquisition is not constant over time and that it has increased in the orthopox lineage (which includes smallpox and vaccinia). We also tested for positive selection on 204 groups of genes and show that a disproportionately high proportion of genes in the orthopox clade are under positive selection. The association of an increased rate of gene gain and positive selection is indicative of adaptive genome evolution. Many of the genes involved in these processes are likely to be associated with host-parasite coevolution.
PUBLISHED
PMID: 14660798
Keywords: Genetics; Genes & Society